1964
DOI: 10.1172/jci104931
|View full text |Cite
|
Sign up to set email alerts
|

Transcortin: A Corticosteroid-binding Protein of Plasma. VII. Half-Life in Normal and Estrogen-treated Subjects *

Abstract: In 1959 we described elevated plasma concentrations of transcortin during pregnancy and after the administration of estrogens (1,2). Since then, a number of investigations utilizing a variety of methodologies to ascertain the binding of cortisol to transcortin have confirmed our observations (3-8). The different techniques used and the diverse arithmetic approaches employed all indicate that the plasma concentration of transcortin rises about threefold during pregnancy or after estrogen therapy. These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Furthermore, a half-life T1 /2 value of about 5 days for CBG has been measured in sheep (Ballard et al, 1982), rats and humans (Sandberg et al, 1964). Our results in newborn guinea-pigs confirm these postnatal changes in CBG .…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, a half-life T1 /2 value of about 5 days for CBG has been measured in sheep (Ballard et al, 1982), rats and humans (Sandberg et al, 1964). Our results in newborn guinea-pigs confirm these postnatal changes in CBG .…”
supporting
confidence: 79%
“…Furthermore, a half-life T1 /2 value of about 5 days for CBG has been measured in sheep (Ballard et al, 1982), rats and humans (Sandberg et al, 1964 (Koch, 1969) or in neonatal rabbits (Sereni et al, 1966). In newborn guinea-pigs, the glucocuronide conjugating system is defective (Brown and Zuelzer, 1958), and Dalle et a/.…”
mentioning
confidence: 99%
“…We have carefully demonstrated that the half-lives of intact and elastase cleaved human CBG in the rabbit are identical and hence not significantly different but much shorter than the 5 days reported in humans [15]. In rabbits it is longer than the half-life (6.8 h) reported for native human CBG in hamsters [16] but shorter than the circulating biological half-life of 13 h reported for 2 forms of rabbit CBG [17].…”
Section: Discussionmentioning
confidence: 60%
“…Corresponding values for the half-time of I131-TBPA in the plasma were 2.67 ± 0.53 days, values in close agreement with those reported by Oppenheimer and colleagues for the terminal slope of I131-TBPA disappearance (12). Thus, TBPA appears to be among the most rapidly turning over of the plasma proteins thus far studied (26,(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%